2008
DOI: 10.1113/jphysiol.2007.139105
|View full text |Cite
|
Sign up to set email alerts
|

Human tendon behaviour and adaptation,in vivo

Abstract: Tendon properties contribute to the complex interaction of the central nervous system, muscle-tendon unit and bony structures to produce joint movement. Until recently limited information on human tendon behaviour in vivo was available; however, novel methodological advancements have enabled new insights to be gained in this area. The present review summarizes the progress made with respect to human tendon and aponeurosis function in vivo, and how tendons adapt to ageing, loading and unloading conditions. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
214
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(236 citation statements)
references
References 81 publications
10
214
0
6
Order By: Relevance
“…Based on the present knowledge about the relation between tendon structure and biomechanical properties (7,37), this novel finding corresponds very well with 1) the observed enhanced tendon synthesis in ERT users, indicating a higher collagen turnover; 2) the fibril characteristics showing a nonsignificant higher fibril density and a lower mean fibril size; and 3) the relative higher numbers of smaller fibrils in ERT users compared with controls. In addition, our observations provide a further clarification of earlier findings, revealing lower maximal load at tissue rupture in ACL from ovariectomized rabbits, which had been exposed to high estrogen levels for 1 mo compared with controls (52).…”
Section: Biomechanical Propertiessupporting
confidence: 61%
See 1 more Smart Citation
“…Based on the present knowledge about the relation between tendon structure and biomechanical properties (7,37), this novel finding corresponds very well with 1) the observed enhanced tendon synthesis in ERT users, indicating a higher collagen turnover; 2) the fibril characteristics showing a nonsignificant higher fibril density and a lower mean fibril size; and 3) the relative higher numbers of smaller fibrils in ERT users compared with controls. In addition, our observations provide a further clarification of earlier findings, revealing lower maximal load at tissue rupture in ACL from ovariectomized rabbits, which had been exposed to high estrogen levels for 1 mo compared with controls (52).…”
Section: Biomechanical Propertiessupporting
confidence: 61%
“…Training and loading influence tendon size and biomechanical properties (29,37). V O 2max and maximal tendon force were higher in control compared with ERT users, but no association was observed between either the mean fibril area, fibril volume fraction, or fibril density, when these parameters were pooled for all subjects and correlated to either V O 2max , muscle strength, or PAL.…”
Section: Tendon Csa and Fibril Characteristicsmentioning
confidence: 99%
“…Usually, larger/stronger tendons are attached to larger/stronger muscles, while smaller and weaker muscles have smaller/weaker tendons (Narici and Maganaris 2007). Regular physical exercise leads to stronger muscle and correspondingly stronger tendon (reviewed in Kjaer et al 2009), while age-related decrease in physical activity and changes in structural composition could be related to weakened tendons and increased risk factor for tendinopathy in the elderly (reviewed in Magnusson et al 2008;Hess 2010). Tendons are composed primarily of collagens that contribute to the ability of the tissue to withstand high tensile forces.…”
Section: Introductionmentioning
confidence: 99%
“…Disuse following immobilization has been associated with decreased levels of extracellular matrix protein expression, alterations in tenocyte morphology, and loss of normal extracellular matrix architecture, resulting in impaired function and healing capacity 14,[95][96][97][98] . Exercise improves the mechanical properties following age and disuse changes [99][100][101] . The ideal exercise program seeks to avoid injury while providing a biologic stimulus to maintain tendon homeostasis and function.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Resistance training utilizing 80% of the five-repetition maximum three times per week for fourteen weeks in elderly individuals was shown to result in a 65% to 70% increase in tendon stiffness aging and/or disuse, incorporating resistance training into exercise regimens may be beneficial 95 . Eccentric strengthening exercise programs have been advocated as effective treatments for tendon overuse injuries and prevention of reinjury [100][101][102][103][104][105][106][107][108] . Arampatzis et al demonstrated that exercises involving high tendon strain (mean and standard deviation, 4.72% ± 1.08%) were more effective than those producing low tendon strain (mean, 2.97% ± 0.47%) in triggering an adaptive response in human Achilles tendon 100 .…”
Section: Clinical Applicationsmentioning
confidence: 99%